Patient Activation Mediates Health Literacy Associated with Hospital Utilization Among Whites - Marjory Charlot; Michael R. Winter; Howard Cabral; Michael S. Wolf; Laura M. Curtis; Amresh Hanchate; Michael Paasche-Orlow (SLACK Incorporated, 2017)
Background: Reducing the 30-day hospital readmission rate is a national priority, and patient activation has emerged as a modifiable target to reduce hospital readmissions. Objective: Prior studies demonstrate that low patient activation and low health literacy are each associated with higher rates of hospital utilization. The aim of this study was to use path analysis methods to assess if patient activation mediates the relationship between health literacy and hospital utilization in the 30 days after discharge. Methods: We performed a secondary analysis of data from a randomized controlled trial of patients receiving care at an urban safety net hospital. Path analyses were used to assess patient activation as a mediator of the relationship of education and health literacy with 30-day hospital utilization. The final model was stratified by race and ethnicity. Key Results: In the overall study sample, a patient activation measure (PAM) score that was one standard deviation (SD) higher was associated with 18% reduced odds of hospital utilization (odds ratio [OR] 0.82; 95% confidence interval [CI] [0.73, 0.91]; p < .001). PAM mediated the relationship between education level and health literacy and hospital utilization. When stratified by race, the mediating effect of PAM was evident among Whites, but not among non-Whites. Specifically, a one SD higher PAM score was significantly associated with a 33% reduced odds of utilization among Whites (OR 0.67, 95% CI [0.57, 0.79], p < .001). With the inclusion of PAM in the model, there was no direct relationship between either health literacy or education and 30-day hospital utilization. Conclusions: Patient activation is only associated with hospital utilization among Whites. Further research is needed to assess if this selective protection is seen in other cohorts. Potential interventions to reduce hospital readmissions may need to consider other modifiable factors in racially and ethnically diverse populations.